Predicting outcomes of early expressive language delay - Paul, R.; Fountain, R. (Infant-Toddler Intervention, 1999)
A group of children was identified as 'late talkers' who were slow in expressive language development (SELD) on the basis of small expressive vocabulary size at 20-34 months of age. The subjects were followed yearly throughout the preschool and early school-age periods in order to track growth in language and related skills. When the subjects were in second grade, their expressive language skills, as indexed by the Developmental Sentence Score, were measured. This measure was used as the outcome variable in regression and discriminant function analyses. Predictor variables included those gathered when the subjects entered the study at age 2. They included measures of early expressive and receptive language by parent report, nonverbal cognitive performance, Bayley Mental Scale score (a combined verbal and nonverbal cognitive measure), phonological skill, motor skills, maladaptive behaviors, social skills, birth order, socioeconomic (SES) level, and gender. Only SES and early expressive language skills predicted expressive language outcome in second grade. Discriminant function analysis revealed these two factors were significant in predicting success (scores above the tenth percentile), along with a contribution of early gross motor skills. The implications of these findings for understanding early language delays are discussed.
Keywords: article; child; child development; clinical article; dept.cmd; developmental disorder; discriminant analysis; female; human; language development; language disability; male; outcomes research; prediction; ⛔ No DOI found

Multiplex developmental disorders: the role of communication in the construction of a self - Paul, Rhea; Cohen, Donald J.; Klin, Ami; Volkmar, Fred R. (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article discusses the integration of various aspects of the child's development, particularly the development of language and communication and the way in which these developments interact to enable the child to construct a coherent sense of self. Multiplex developmental disorder is presented as an example of a disorder that affects several of these crucial strands of development. Recent research and controversies regarding the diagnostic descriptions of multiplex and other pervasive developmental disorders are presented. This discussion is used to illustrate the ways in which such disorders affect not only the individual aspects of development, but the child's ability to form a cohesive sense of self. The implications of these difficulties in self-definition for treating children with disorders that affect a variety of aspects of development are also discussed.
Keywords: *Communication Disorders/di [Diagnosis]; *Developmental Disabilities/di [Diagnosis]; Child; Child Development Disorders, Pervasive/co [Complications]; Child Development Disorders, Pervasive/di [Diagnosis]; Child Development Disorders, Pervasive/px [Psychology]; Child, Preschool; Communication Disorders/et [Etiology]; Communication Disorders/px [Psychology]; Developmental Disabilities/co [Complications]; Developmental Disabilities/px [Psychology]; Humans; Infant; Language Development; affective neurosis; attention deficit disorder; autism; child; cognitive defect; communication disorder; dept.cmd; developmental disorder; disease association; human; mental disease; mental performance; neuropsychiatry; priority journal; review; schizophrenia; social behavior; symptomatology

Communication disorders and children with mental retardation - Cascella, Paul W (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article examines the communication styles of children with mental retardation, emphasizing the assessment and intervention protocols used by health and education professionals. This article highlights the following approaches: a developmental psycholinguistic orientation, a pragmatics approach, and a supportive interdependent format consistent with the 1992 revision of how mental retardation is classified. This article discusses children with mental retardation who show challenging and disruptive behavior.
Keywords: *Communication Disorders/co [Complications]; *Intellectual Disability/co [Complications]; Child; Child, Preschool; Communication Disorders/di [Diagnosis]; Communication Disorders/rh [Rehabilitation]; Humans; Infant; Infant, Newborn; Intellectual Disability/rh [Rehabilitation]; Language Tests; Models, Psychological; Psycholinguistics; auditory memory; communication disorder; dept.cmd; interpersonal communication; language; learning; mental deficiency; priority journal; recall; review; social interaction

Assessing communication in children with psychiatric and communication disorders - Kennedy, MD (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article presents issues related to the communication assessment of children with psychiatric and communication disorders. Challenges inherent in assessing this population are discussed. Frequently used assessment instruments and procedures are described. Consideration is given to the assessment of very young or low-functioning children and older or high-functioning children.
Keywords: *Communication Disorders/di [Diagnosis]; *Language Tests; *Mental Disorders/co [Complications]; *Psychometrics/mt [Methods]; Adolescent; Asperger syndrome; Child; Child Development Disorders, Pervasive/co [Complications]; Child Development Disorders, Pervasive/di [Diagnosis]; Child, Preschool; Communication Disorders/co [Complications]; Humans; Male; Mental Disorders/di [Diagnosis]; adolescent; case report; communication disorder; data analysis; dept.cmd; developmental disorder; differential diagnosis; human; intelligence; language ability; male; mental disease; mental task; phonetics; priority journal; problem solving; psychiatric diagnosis; review; school child; speech articulation; speech therapy; standardization; verbal communication

Child and Adolescent Psychiatric Clinics of North America: Preface - Paul, R. (Child and Adolescent Psychiatric Clinics of North America, 1999)
Keywords: attention deficit disorder; autism; behavior disorder; child psychiatry; cognitive defect; communication disorder; dept.cmd; editorial; mental deficiency; mental disease; priority journal; reading; speech disorder

Discussion: Early speech perception and production - Paul, R. (Journal of Communication Disorders, 1999)
Keywords: Communication Disorders; Humans; Infant; Infant Behavior; Language Development; Parents; Verbal Behavior; conference paper; dept.cmd; human; infancy; infant; language development; speech development

Assessing speech, language, and communication - Paul, R.; Marans, W.D. (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article discusses the assessment of communication skills in children from birth to 5 years of age. The different methods appropriate for different developmental levels and the relationship of collateral areas, such as hearing, cognition, and speech motor control to the communication process, are addressed. The need for standardized and informal measures is emphasized Case studies are presented to illustrate the principles outlined.
Keywords: *Language Development Disorders/di [Diagnosis]; *Mental Disorders/co [Complications]; *Speech Disorders/di [Diagnosis]; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Language Development Disorders/pc [Prevention & Control]; Language Development Disorders/px [Psychology]; Language Tests; Male; Mental Disorders/di [Diagnosis]; Nonverbal Communication; Psycholinguistics; Speech Disorders/px [Psychology]; child; child development; dept.cmd; human; infant; intelligence; language disability; medical record; mental disease; priority journal; review; skill; speech articulation; speech disorder; verbal communication

Communication and its disorders - Paul, R.; Rubin, E. (Child and Adolescent Psychiatric Clinics of North America, 1999)
This article defines communication and describes its various disorders. Some of these disorders are associated with other DSM-IV conditions, such as mental retardation or pervasive developmental disorder. Others are specific to the language-learning process. The interactions between communication and psychiatric disorders are discussed. Suggestions for integrating treating approaches among communication disorders and mental health professionals are presented.
Keywords: *Communication Disorders; Child; Child Abuse; Child Development; Communication Disorders/ep [Epidemiology]; Communication Disorders/et [Etiology]; Communication Disorders/px [Psychology]; Comorbidity; Female; Humans; Infant; Infant, Newborn; Mental Disorders/ep [Epidemiology]; Nervous System Diseases/co [Complications]; Pregnancy; Prenatal Exposure Delayed Effects; Socioeconomic Factors; affective neurosis; autism; brain injury; cerebrovascular accident; child abuse; cocaine; communication disorder; cultural anthropology; dept.cmd; developmental disorder; economic aspect; fetal alcohol syndrome; hearing impairment; interpersonal communication; language disability; mental deficiency; mental disease; mutism; prenatal drug exposure; priority journal; review; social problem; speech disorder; visual impairment